Addition of Beetroot Extract to Neoadjuvant Adriamycin Cyclophosphamide Regimen Increased Tumor Cell Apoptosis in Mammary Adenocarcinoma Rats - Susilowati, Sri; Susilaningsih, Neni; Suharti, Catharina (Indonesian Journal of Cancer Chemoprevention, 2021)
Apoptosis is one of the anticancer targets. Currently, the concomitant use of phytotherapy products and chemotherapy regimens is common in breast cancer patients. The purpose of this study was to examine the apoptotic effect of adding beetroot extract to the neoadjuvant Adriamycin Cyclophosphamide (AC) regimen by observing the expression levels of p53 and caspase 3 in tumor tissue from mammary adenocarcinoma rats. Twenty-four rats that succeeded in growing tumor nodules were randomly divided into 4 treatment groups: without treatment, AC only treatment, AC plus beetroot extract at dose of 25 and 100 mg/kg BW, respectively. AC was given 4 cycles in doses of 5 and 50 mg/kg body weight intraperitoneally every week. Tumor tissue was dissected at 4th week for examination of p53 and caspase 3 expression levels using the qRT-PCR method. The addition of beetroot extract at doses of 25 and 100 mg/kg BW in the neoadjuvant AC regimen showed significantly higher levels of p53 and caspase 3 expression than those with AC treatment alone. These results proved that beetroot extract has a synergistic effect with neoadjuvant AC regimen by increasing tumor cells apoptosis.Keywords: Beetroot extract, Adriamycin, Cyclophosphamide, apoptosis, p53.